Analisis upaya guru dalam penguatan karakter profil pelajar pancasila dimensi gotong royong pada pembelajaran ekstrakurikuler pramuka - Nugraheni, Septia Luthfi; Matsuri, Matsuri; Saputri, Dwi Yuniasih (Didaktika Dwija Indria, 2025)
This study aims to determine how the teacher's efforts in strengthening the character of mutual cooperation in extracurricular scout learning. This is motivated by recent cases that have affected the quality of Indonesian education due to the low moral values of students. This research uses a qualitative approach descriptive method with data sources of the principal, extracurricular scout teachers and grade IV students at SDN 2 Kalikebo, Trucuk, Klaten. Data were collected through three techniques, namely observation, interviews and document studies for four meetings. Data analysis used interactive analysis techniques by Miles and Huberman. The results of this study show several teacher efforts that can fulfill the indicators of the gotong royong character. This research can add insight for teachers and prospective teachers in implementing character strengthening, both the character of gotong royong and other characters.